Synthesis and Biological Evaluation of 4‐Arylphthalazones Bearing Benzenesulfonamide as Anti‐Inflammatory and Anti‐Cancer Agents. Issue 6 (7th May 2013) - Yaseen, Shafiya; Ovais, Syed; Bashir, Rafia; Rathore, Pooja; Samim, Mohammed; Singh, Surender; Nair, Vinod; Javed, Kalim
Abstract Nine 4‐arylphthalazones bearing benzenesulfonamide (2a–i) were synthesized by the condensation of the appropriate 2‐aroylbenzoic acid (1a–i) and 4‐hydrazinobenzenesulfonamide in ethanol. The structures of these compounds were elucidated by elemental analysis, IR, 1H NMR, 13C NMR, and MS spectroscopy. Two compounds, 2b and 2i, showed significant anti‐inflammatory activity comparable to that of the standard drug celecoxib in the carrageenan‐induced rat paw edema model. These compounds (2b and 2i) had selective inhibitory activity towards the COX‐2 enzyme. Compound 2b had a better selectivity ratio (COX‐1/COX‐2) compared to that of celecoxib and can be used as a novel template for the design of selective COX‐2 inhibitors. Compounds 2d and 2i were screened for their antiproliferative activity towards 60 human cancer cell lines by the National Cancer Institute (USA). The compounds 2d and 2i displayed mild activity toward the renal cancer cell line UO‐31.